The effects of circuit hydraulic weight interval training on body composition and progression of resistance in recreationally exercising pre- and postmenopausal women: an 18-week quasi-experimental study - Socha, Małgorzata; Ćwieląg, Paulina; Andrzejewski, Waldemar (Frontiers in Physiology, 2025)
BackgroundThe lack of physical activity, stress, and unhealthy eating habits contribute to body mass disorders, which form the basis of most civilization diseases. Mature women are increasingly turning to fitness clubs to improve their physique and protect themselves from diseases and the progressive aging process. The multitude of training systems proposed to women by fitness clubs leads to the search for solutions that will bring positive health results. The response to an exercise stimulus may depend on the menopausal status.MethodsThis quasi-experimental study aimed to determine the effects of 6, 12, and 18 weeks of circuit hydraulic weight interval training (CHWIT) on anthropometric indices, body composition estimated by the bioelectrical impedance analysis (BIA), and muscle performance in inactive pre- and post-menopausal women from an urban population. A total of 100 women aged between 35 and 69 (mean 51.5 ± 9.61) years with a mean body mass index (BMI) of 27.3 (±5.4 kg/m2) were divided by menopausal status and assigned to the training CHWIT group (25 pre- and 25 postmenopausal women) and the control group (25 pre- and 25 postmenopausal women). Each participant from the CHWIT group took part in a total of 54 training sessions, developed for the Mrs.Sporty network, under the constant supervision of a qualified trainer.ResultsAfter 18 weeks of training in both intervention groups, ANCOVA demonstrated statistically significant (p < 0.05) decreased body fat (%), reduced thigh and arm circumference, and increased muscle component (kg) as the main part of fat-free body mass. Additionally, premenopausal women decreased their body mass, BMI, and waist and hip circumferences. A significant increase in the muscle component was noticed after 6 weeks of CHWIT in pre-menopausal women and only after 18 weeks in postmenopausal women. Significant progression of resistance (amount of repetitions on hydraulic machines) was observed after 6 weeks and at each subsequent stage of CHWIT in both intervention groups (p < 0.001). No significant differences were found in the controls.ConclusionCHWIT is an effective form of training, improving body composition and physical functions in inactive pre- and postmenopausal women. Changes in the muscle component require a longer intervention of physical effort in women after menopause.